Normas jurídicas concessivas de incentivos fiscais e as facultatividades no direito tributário brasileiro - Alves, Maíza Costa de Almeida (2016)
The Brazilian law system has an unspecified number of laws destined to discipline inter-subjective actions and to achieve social values. Under tax laws, these rules shall be responsible for ensuring the tax collection for the State but also for other objectives to be acomplished in order to promote economic and social development of the country. The prescriptivity of the law on taxpayers makes the payment of taxes a compulsory obligation. So long as the individual rights are respected, the State has the right and duty to demand such exactions. Faced with this compulsory obligations related to taxes, the positive system of laws also provides its own mechanisms of reliefing tax burden, by option, which aim to encourage the taxpayer s actions towards the completion of legal principles. These mechanisms are called tax incentives, which are the object of this work. Using the philosophy of language, legal semiotics, deontic logic and the theory of law, it was possible to approach the structure of incentive tax law and then to invetigate it through their logical, semantic and pragmatic features, also demonstrating the importance of voluntary rules in tax law. As opposed to compulsory obligations, the incentive tax law is an alternative to the common tax rules, rules that offer a more beneficial taxation for the discharge of specific behaviors. Over the studies developed in this work, it was an objective give the reader a more organized understanding of the structure of incentive tax laws so that it becomes clear assessment of their legality or constitutionality. Indeed, the alternative application of these laws in opposition to the ordinary tax law can not provide damages to the taxpayer under penalty of illegality or unconstitutionality